Światowy kryzys finansowy jako katalizator integracji krajów Azji Wschodniej - Szuster, Mariusz (The world financial crisis as a catalyst of the integration of East Asian countries, 2009)
The Asian countries depend seriously on the export US and EU-bound. This became a source of economic problems. The integration of countries of the region is perceived as a chance for them to overcome crisis. The increased trade is a proof of such an assumption. There are plans of ASEAN Economic Community creation and also plans of further trade intensification. There are also obstacles like differences among these countries. These barriers may slow or even stop the process of integration
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 72-79